INVESTIGATION OF SUSPECTED PERIPHERAL NEUROPATHY OUTBREAK IN DECHENTSEMO CENTRAL SCHOOL, THINLEYGANG, PUNAKHA - ten, Tshe; Dzed, Laigden; Thinley, Sangay; Tshomo, Deki; Dechen, Karma; mo, Zang; Mongar, Dhan Bdr; Palzang, Thupten; Yangzom, Karma; Gyeltshen, Tandin; Choki, Pema; Wangchuk, Sonam (Public Health of Indonesia, 2016)
Background: A suspected peripheral neuropathy outbreak was reported from Dechentsemo Central School, Thinleygang, Punakha, following which the investigation team was immediately dispatched in the field.Objective: The aim of investigation was to ascertain the cause and risk factor for the outbreak in order to implement control measures.Methods: A case control study was devised for the investigation to study about the past exposure or deficiencies in order to find out the suspected cause and risk factors.  A semi-quantitative food frequency questionnaire was administered to both cases and controls to collect information on the type of food they have consumed. The information garnered was analyzed using Chi-Square or Fischer Exact test for categorical variables and Man-Whitney U-test for quantitative variables. Results: All 17 cases were females with mean age of 13 years (SD 2.7 years). The average daily amount of thiamine intake was 0.6 mg/day for case and 0.8 mg/day for controls against the recommended daily allowance (RDA) of 1.2 mg/day. Case and control patients differed significantly with respect to fat intake (p-value = 0.02), more strongly with folate and iron intake (p-value < 0.01).Conclusion: The outbreak of peripheral neuropathy in Dechentsemo Central School appears to be linked to reduced dietary intake rich in vitamin B1 coupled with low intake of folate and iron in their diet.